Inactivation of dengue, chikungunya, and Ross River viruses in platelet concentrates after treatment with ultraviolet C light. Issue 6 (1st March 2016) - Faddy, Helen M.; Fryk, Jesse J.; Prow, Natalie A.; Watterson, Daniel; Young, Paul R.; Hall, Roy A.; Tolksdorf, Frank; Sumian, Chryslain; Gravemann, Ute; Seltsam, Axel; Marks, Denese C.
Abstract : BACKGROUND: Arboviruses, including dengue (DENV 1‐4), chikungunya (CHIKV), and Ross River (RRV), are emerging viruses that are a risk for transfusion safety globally. An approach for managing this risk is pathogen inactivation, such as the THERAFLEX UV‐Platelets system. We investigated the ability of this system to inactivate the above mentioned arboviruses. STUDY DESIGN AND METHODS: DENV 1‐4, CHIKV, or RRV were spiked into buffy coat (BC)‐derived platelet (PLT) concentrates in additive solution and treated with the THERAFLEX UV‐Platelets system at the following doses: 0.05, 0.1, 0.15, and 0.2 J/cm 2 (standard dose). Pre‐ and posttreatment samples were taken for each dose, and the level of viral infectivity was determined. RESULTS: At the standard ultraviolet C (UVC) dose (0.2 J/cm 2 ), viral inactivation of at least 4.43, 6.34, and 5.13 log or more, was observed for DENV 1‐4, CHIKV, and RRV, respectively. A dose dependency in viral inactivation was observed with increasing UVC doses. CONCLUSIONS: Our study has shown that DENV, CHIKV, and RRV, spiked into BC‐derived PLT concentrates, were inactivated by the THERAFLEX UV‐Platelets system to the limit of detection of our assay, suggesting that this system could contribute to the safety of PLT concentrates with respect to these emerging arboviruses.